Analysis of the Impact of Digitalization on MSME Economic Growth in Indonesia - Meidyasari, Sofi (Sahabat Publikasi, 2024)
Digitalisation has changed how businesses operate, including in Indonesia's Micro, Small and Medium Enterprises (MSMEs) sector. This study aims to analyse the impact of digitalisation on the economic growth of MSMEs. Qualitative research is the method used in this research, and data is collected through literature studies and relevant previous reports on the effect of digitalisation on MSMEs. Once the data is collected, the analysis process is conducted through several stages, including data filtering, presentation, and conclusion drawing. The results obtained explain that digitalisation has a positive impact on the economic growth of MSMEs in Indonesia. Digitalisation has great potential to help improve the economic growth of MSMEs by expanding markets, improving operational efficiency, and encouraging innovation in products. However, to maximise these benefits, MSMEs face various challenges in the digitisation process, such as limited access to technology and a lack of skills in using digital technology. Thus, there is a need for collaboration between the government, businesses, and the community to overcome these challenges so that MSMEs in Indonesia have the potential to become the main pillar of the national economy